A Systematic Review on the Existing Screening Pathways for Lynch Syndrome Identification - Tognetto, Alessia; Michelazzo, Maria Benedetta; Calabró, Giovanna Elisa; Unim, Brigid; Di Marco, Marco; Ricciardi, Walter; Pastorino, Roberta; Boccia, Stefania (Frontiers in Public Health, 2017)
Background Lynch syndrome (LS) is the most common hereditary colon cancer syndrome, accounting for 3–5% of colorectal cancer (CRC) cases, and it is associated with the development of other cancers. Early detection of individuals with LS is relevant, since they can take advantage of life-saving intensive care surveillance. The debate regarding the best screening policy, however, is far from being concluded. This prompted us to conduct a systematic review of the existing screening pathways for LS. Methods We performed a systematic search of MEDLINE, ISI Web of Science, and SCOPUS online databases for the existing screening pathways for LS. The eligibility criteria for inclusion in this review required that the studies evaluated a structured and permanent screening pathway for the identification of LS carriers. The effectiveness of the pathways was analyzed in terms of LS detection rate. Results We identified five eligible studies. All the LS screening pathways started from CRC cases, of which three followed a universal screening approach. Concerning the laboratory procedures, the pathways used immunohistochemistry and/or microsatellite instability testing. If the responses of the tests indicated a risk for LS, the genetic counseling, performed by a geneticist or a genetic counselor, was mandatory to undergo DNA genetic testing. The overall LS detection rate ranged from 0 to 5.2%. Conclusion This systematic review reported different existing pathways for the identification of LS patients. Although current clinical guidelines suggest to test all the CRC cases to identify LS cases, the actual implementation of pathways for LS identification has not been realized. Large-scale screening programs for LS have the potential to reduce morbidity and mortality for CRC, but coordinated efforts in educating all key stakeholders and addressing public needs are still required.